A Kaleckian model of growth and distribution considering the effects of the urban informal sector. Issue 1 (2nd January 2023) - Paiva, Henrique; Oliveira, João Gabriel; Teixeira, Joanilio
Abstract: In this paper we present an effort to integrate the informal sector into a neo-Kaleckian growth and distribution model. While informality is a relevant issue to all developing countries, our work is motivated mainly by the Brazilian case, where recent growth of informal employment occurs amid stagnation of the formal sector. We seek to shed light on the relationship between the expansion of both sectors and their influences on economic performance, using as theoretical background the reproduction scheme from Kalecki, now considering the informal sector into the model. Also, we seek to examine the extent to which the expansion of the informal activities can be helpful or harmful for the formal economy in the long run. Our model is consistent with observed empirical facts and reinforces some theoretical and empirical results, for instance, the resilience of the informal activity, its growth at times of economic expansion as well as in times of recession, and its ultimate dependence on the formal economy.